Financial Statements of Micro, Small and Medium Enterprises (MSMEs) Based on SAK Indonesia for EMKM - Evinita, Lenny Leorina; Moroki, Florence Olivia; Pangajouw, Vilya Vebrianti (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Net Coffee and Resto is a business engaged in food and beverage or culinary services located on Jalan Raya Pasar Baru, Waleure, East Langowan District, Minahasa Regency, which has been operating since June 2021. This study aims to analyze what Net Coffee and Resto financial statements are based on SAK Indonesia for EMKMs. This type of research uses descriptive analysis with a qualitative approach. The data collection used in this study is observation, interviews, and documentation. The results of the study show that Net Coffee and Resto MSMEs have not implemented financial statements under SAK Indonesia for EMKMs, because they only present Income Statements, Sales Reports, and Expenditure Reports. Meanwhile, the financial statements based on SAK Indonesia for EMKM consist of Financial Position Statement (Balance Sheet), Profit and Loss Report, and Notes on Financial Statements. Net Coffee's profit and loss recording also does not separate between principal expenses and operating expenses, nor does Net Coffee recognize rental costs on expenses. The obstacles faced are the lack of understanding of SAK Indonesia for EMKMs, the lack of expertise to prepare financial statements under SAK Indonesia for EMKM and the limited time that informants have.